Soil organic matter and CO.sub.2 fluxes in small tropical watersheds under forest and cacao agroforestry - Costa, Eline Nayara Dantas da; Landim de Souza, Marcelo Friederichs; Lima Marrocos, Paulo Cesar; Lobão, Dan; Lopes da Silva, Daniela Mariano (PloS one, 2018)
Annual estimates of CO.sub.2 and dissolved carbon concentrations in the soil profile provide valuable insight into the dynamics of organic matter in soil and the effect of changes to vegetation cover. The aim of this study was to observe the spatial influence of litter decomposition in the first few centimeters of the soil for CO.sub.2 fluxes and to describe the processing of soil organic matter throughout the soil profile by comparing three small tropical watersheds. Data were collected biweekly for six months, from December 2015 to May 2016. CO.sub.2 was measured using an infrared gas analyzer in fixed chambers and the dissolved carbon of soil solution was analyzed in a TOC analyzer. No differences were found in the total soil CO.sub.2 fluxes (control flux treatments) between the three study areas. In both cacao agroforestry systems (managed and unmanaged), total CO.sub.2 fluxes were influenced by the decomposition of litter. CO.sub.2 emissions in the soil profile of the cacao agroforestry systems were highly variable, compared to the preserved forest, and highly dependent on the soil characteristics attributed to the type of vegetation cover. Although a definite pattern between the temperature and soil moisture was not identified, these parameters showed a strong relationship in controlling the release of CO.sub.2 between treatments. The organic and inorganic dissolved carbon patterns in the soil solution of the three areas revealed different responses of soil organic matter processing related to soil characteristics and vegetation. The results confirm the hypothesis that the top of soils (total CO.sub.2 fluxes) of both cacao agroforestry systems (managed and unmanaged) emits fluxes of CO.sub.2, which do not differ statistically from the preserved forest. However, depending on the soil characteristics, the cacao agroforestry system can result in an accumulation of CO.sub.2 and dissolved inorganic carbon in the soil profile that is prone to being transported by hydrological routes to groundwater and stream water.